Dynamic Attendance Marking System Using Combination of Physical Presence And Real Time Monitoring - C. Jayavarthini, Ashwani Kumar Sinha , Avinash Jha (International Journal of Advanced Science and Technology, 2020)
The issue of data contact between an instructor and understudies is one of the most significant in almost a wide range of classes, for example, talks, courses and functional classes in the research centres. This issue is normal of practically all degrees of instruction, starting from pre-school to studying at college and graduate institution. As its’ a matter in question, we are developing a model to monitor the physical state of students in the concerning classes. A proper monitoring will be done in x number of sessions during a particular period of class and on the basis of each session, a dynamic attendance will be taken for each of the students. The algorithm to be used is of face detection and other libraries. The expected outcome of this project is to generate the report of dynamic attendance in order to create attentiveness among students and make the efforts of teachers more efficient with better throughput.